Disentitlement? : the threats facing our public health-care programs and a rights-based response - Jost, Timothy S. (Oxford University Press, 2003)
No developed nation relies exclusively on the private sector to finance health care for citizens. This book begins by exploring the deficiencies in private health insurance that account for this. It then recounts the history and legal character of America's public health care entitlements - Medicare, Medicaid, and tax subsidies for employment-related health benefits. These programs are increasingly embattled, attacked by those advocating privatization (replacing public with private insurance), individualization (replacing group and community-based insurance with approaches based on individual choice within markets) and devolution (devolving authority over entitlements to state governments and to private entities). The book critically analyzes this movement toward disentitlement. He also examines the primary models for structuring health care entitlements in other countries - general taxation-funded national health insurance and social insurance, and considers what we can learn from these models.; The book concludes by describing what an American entitlement-based health care system could look like, and in particular how the legal characteristics of our entitlement programs could be structured to support the long-term sustainability of these vital programs.